Design-Project in Television (Herald of Journalism, 2019)
The article studies the role of design in modern television, the problems and features of the televi-sion profession, its goals and influence on the channel’s rating and audience. Television is one of the most important tools of information, entertainment and communication of a person with the world. Despite the advent of the Internet, people still rely on television. The advantages of choosing television channels for an audience are based on the principle of finding information that they are interested in. TV design directly affects the rating of TV channels. This article describes the roles and responsibilities of the television designer profession, which should be considered when training future professionals. Television affects people, gives them certain values and​ ideals. Therefore, taking part in this complex, multi-level process, one need to understand that design is socially influential in the production of a particular prod-uct. Using an aesthetically pleasing image corresponds to thematic channels and requires proper graph-ics processing. The article is devoted to the general television industry, its location and its main focus. The article will have its role for use in the field of television.
Keywords: television design, television, computer technology, design training.